Ask the Young: What Homeschooled Adolescents Think About Homeschooling. Issue 4 (1st October 2020) - Neuman, Ari
ABSTRACT: Home schooling is a growing practice in many Western countries. Examination of the practice has entailed collection of "hard" data, such as academic achievements and success rates in higher education, as well as investigation of the practice from the perspective of parents. It is very important to examine homeschooling from the perspective of the children studying in this framework, yet only a few studies of this type have been conducted. The purpose of the present research was to examine how adolescents evaluate homeschooling. Semi-structured, in-depth interviews were conducted with 19 young people (ages 16–22) who were raised in a homeschooling setting. The interviews included a series of questions intended to examine how adolescents evaluate homeschooling. The findings indicated diverse themes that can be divided into four main super-themes: contents and methods of instruction and learning; outcomes – traits; outcomes – family; and outcomes – society. Regarding the first super-theme, the interviewees noted both advantages and disadvantages. For the second and third themes, they cited only advantages. With regard to the fourth theme, only disadvantages were mentioned. The findings suggest that some of the themes refer to constructivist learning and some of them reflect overall aims of education – socialization and individuation.